Implementasi Sistem Penilaian Kinerja Karyawan Dengan Menggunakan Metode AHP-TOPSIS Untuk Rekomendasi Pemilihan Karyawan Tetap - Dedi Romario; Fitra Abdurrachman Bachtiar; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The role of the workforce as Human Resources (HR) that runs operational tasks within the company has an important role in the success of the company. To get a competent workforce it is necessary to conduct an assessment process for the workforce to be appointed as permanent employees in a company. It is also applied by one of the companies in the field of express courier and logistics PT. Tiki Jalur Nugraha Ekakurir or commonly known as JNE. To reduce subjectivity in the assessment process it is necessary to give weighting to each criterion to be used in the assessment process. Analytical Hierarchy Process - Technic for Preference Order by Similarity to Ideal Solution method is one of the combined methods that can help to support decisions in recommending employees. Where AHP is applied to look for priority weights criteria and TOPSIS is applied to rank alternative employees. Accuracy testing is done by using comparison criteria data provided by JNE. The test data used is data from employee recommendations in 2017 as many as 33 employee recommendation data. The results of accuracy testing conducted found that the system's accuracy rate was 69% for permanent employee recommendations, 50% for contract extension, and 80% for contract termination recommendations. In the system acceptance test using the SUS method the value obtained is 80 which in the range of values is the range of